Additive manufactured portable vertical axis windmill. Issue 6 (11th May 2020) - Senthilkumar, P. B.; Logesh, K.; Bhanderi, Mitesh Mansukhbhai; Goyal, Vikas; Randeep, S.; Arya, Amankumar
ABSTRACT: The vertical axis windmill is a type of wind turbine in which the main rotor shaft is set vertically. The main aim of this is to make it more compatible and accessible. According to the research, there is plenty of enough wind available globally to meet the human energy requirements – if it is harvested on a large scale effectively. If the wind turbine efficiency is increased, then there is a chance for more power generation and to drastically decrease the use of power generators which are rather expensive and also cause pollution. In comparison to horizontal axis wind turbines, the vertical axis wind turbines may be efficient as them and are also cheaper to build and maintain. In this paper, we designed and fabricated a vertical axis wind turbine and fabricated the same using the '3D printing technique' which is one of the additive manufacturing processes used now.